Flooded parking air conditioner battery capable of meeting short-distance driving requirement

By using Mg-Zn-Al alloy, TBAB to improve positive electrode formula, plastic-grade conductive carbon black and fiberglass bag partitions in commercial vehicle batteries, the problems of confusion in commercial vehicle battery management and low charging efficiency have been solved, and the problem of "confusion in commercial vehicle battery management" and "low charging efficiency" has been extended. Battery life reduces lead consumption costs and improves charging efficiency and user experience.

CN119170892APending Publication Date: 2024-12-20CAMEL GROUP HUAZHONG BRANCH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411435317.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-15
Publication Date
2024-12-20

AI Technical Summary

Technical Problem

The heavy truck industry of commercial vehicles has problems such as chaotic battery management, irregular inventory management, unconformity of battery standards, diversified warranty requirements, and low charging efficiency and fast capacity decay of short-distance vehicles, resulting in early battery failure and high-frequency replacement. .

Method used

Using Mg-Zn-Al new alloy positive electrode plate gate alloy, tetrabutyl ammonium bromide (TBAB) to improve the positive electrode formula, plastic grade conductive carbon black optimized negative electrode formula, glass fiber bag separator and benzyl silicone oil to improve the electrolyte. Combined with flexible phase change materials to treat the battery tank surface, improve the high-temperature mechanical properties, charging efficiency and cycle life of the battery.

Benefits of technology

It reduces lead consumption costs, extends the battery's cycle life, improves dynamic normal temperature charging capacity and low SOC cycle performance, reduces battery return rate, and improves the user experience of end customers.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure BDA0005084774100000021
    Figure BDA0005084774100000021
  • Figure BDA0005084774100000031
    Figure BDA0005084774100000031
Patent Text Reader

Abstract

According to the rich liquid parking air conditioner battery capable of meeting the short-distance driving requirement, a positive electrode formula comprises the following components in parts by weight: 100 parts of lead powder, 8 to 9 parts of dilute sulphuric acid, 10 to 13 parts of deionized water, 0.12 to 0.15 part of tetrabutylammonium bromide (TBAB), 0.1 to 0.12 part of ultra-short fiber, 10 to 13 parts of red lead and 0.06 to 0.10 part of sodium perborate. The negative electrode formula comprises the following components in parts by weight: 100 parts of lead powder, 7-9 parts of dilute sulphuric acid, 9-12 parts of deionized water, 0.08-0.12 part of ultra-short fibers, 0.6-1.2 parts of plastic-grade conductive carbon black, 0.35-0.4 part of high-purity humic acid and 0.6-0.9 part of barium sulfate; the optimized negative electrode formula can improve the conductivity between active substances and improve the dynamic normal-temperature charging acceptance performance of the battery. And aluminum acetylacetonate is added into the electrolyte, so that the continuous discharge capability in a deep discharge environment is improved. According to the invention, the problems of long-term deep discharge and shallow charge of lead-acid rich liquid parking air conditioner storage batteries of short-distance running vehicles and low charging efficiency are solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of lead-acid batteries and relates to a liquid-flooded parking air-conditioning battery that meets the needs of short-distance driving. Background Art

[0002] With the improvement of living standards, commercial vehicle users have increasing demands for vehicle functions. In order to increase the selling points of vehicles, commercial vehicle OEMs are gradually incorporating the needs of end customers to install additional electrical appliances such as induction cookers, electric blankets, and even air conditioners into the normal use of vehicles. The commercial vehicle "parking air conditioner" market is rapidly rising across the country, covering a variety of driving scenarios such as trucks, vans, engineering vehicles, and RVs. For commercial vehicle parking air conditioner models, the market has successively developed lead-acid flooded parking air conditioner batteries, lead-acid AGM parking air conditioner batteries, and lithium batteries for starting parking air conditioners.

[0003] At the same time, the commercial vehicle heavy truck industry currently has the following problems:

[0004] ① The management of the commercial vehicle and heavy truck battery industry is chaotic, and customers’ requests for additional electrical appliances do not match the batteries;

[0005] ② The commercial vehicle inventory is large, the inventory time is long, and the inventory management is not standardized (the negative terminal wire is not unplugged, there is no charging maintenance, etc.);

[0006] ③ The battery standards and adaptability used by various OEMs have not formed a unified specification;

[0007] ④ Each OEM (SINOTRUK, Dongfeng Commercial Vehicle, Foton Daimler, etc.) puts forward a request for extended warranty;

[0008] ⑤ In terms of aftermarket sales, various electrical appliances are installed, and batteries face diversified application scenarios.

[0009] Compared with lead-acid AGM and lithium-ion parking air conditioning batteries for starting, lead-acid flooded parking air conditioning batteries can meet 90% of market demand. For short-distance vehicles, the single use time of the parking air conditioning is 4-6 hours, and it takes 4-10 hours to fully charge the vehicle at constant voltage. However, short-distance vehicles usually travel for 2-3 hours. Under the condition of high power consumption of electrical appliances, the battery is deeply discharged and shallowly charged, and the charging efficiency is low. In addition, the driver does not use it in a standardized manner, and the battery fails prematurely due to sulfurization of the positive plate due to insufficient charging.

[0010] The flooded parking air conditioning battery has the following problems:

[0011] ①High lead consumption cost;

[0012] ② After long-term deep discharge, the positive electrode active material tends to soften and fall off, and the capacity decays rapidly.

[0013] ③ The amount of electrolyte is insufficient, the mixed acid density is high, and the water loss during use in high temperature environment in summer aggravates the growth and corrosion rate of the positive electrode grid.

[0014] ④ The national standard charging is tested under a 0℃ environment. The parking air conditioner is generally used in summer and cannot fully reflect the actual use of end customers.

[0015] ⑤ If the vehicle is started immediately after a long period of low SOC, dendrite penetration may occur on the partition.

[0016] Based on the actual usage scenarios of commercial vehicles, end customers are unable to perform regular battery maintenance and care. Lead-acid flooded parking air-conditioning batteries are discharged deeply and charged shallowly for a long time, with low charging efficiency, fast battery failure and high return rate. On the one hand, this causes economic losses to battery manufacturers; on the other hand, batteries fail quickly and end customers need to frequently replace batteries, causing economic and time losses to end customers, which brings them a bad user experience. Summary of the invention

[0017] The present invention solves the problem of long-term deep discharge and shallow charge of lead-acid flooded parking air-conditioning batteries for short-distance vehicles, and low charging efficiency, and provides a flooded parking air-conditioning battery that meets the needs of short-distance driving, improves battery performance, thereby improving the comfort of end customers and reducing unnecessary quality return losses. The lead consumption cost of the present invention is low, the capacity decay is slow, and the water loss rate is low. At the same time, the battery's 30% SOC-90% SOC dynamic charging acceptance capacity and 30% SOC-40% SOC cycle life at room temperature are improved.

[0018] The problem described in the present invention is achieved by the following technical solution:

[0019] A flooded parking air conditioning battery that meets the needs of short-distance driving. It includes the optimization design of positive grid alloy, the optimization design of positive electrode formula, the optimization design of negative electrode formula, the optimization design of active material ratio, the optimization design of separator type, the optimization design of electrolyte research and optimization design, and the optimization design of battery slot surface treatment materials.

[0020] The positive electrode grid alloy is optimized and designed, using a new Mg-Zn-Al alloy. The Ca content of the grid alloy is appropriately increased, which will form an intermediate phase with a very high melting point in the matrix. These phases are not easy to decompose at high temperatures, and can effectively prevent grain boundary movement, so that the high-temperature mechanical properties of the alloy, especially the creep resistance, are significantly improved. At the same time, appropriately increasing the Ag content can effectively reduce the water loss rate of the electrolyte. Improve the growth and corrosion resistance of the grid, thereby extending the battery cycle life. And it has excellent casting performance and low cost. The mass percentages of the alloy components are as follows:

[0021]

[0022] The positive electrode formula is optimized and designed, and tetrabutylammonium bromide (TBAB) powder organic salt is added to the lead paste formula, which is a phase transfer catalyst that can transfer reactants from the aqueous phase (or organic phase) to the organic phase (or aqueous phase). The retention value of the anion is increased, and the separation degree of the anion and the coexisting ion is also increased. In turn, the voltage platform during battery charging is reduced, the charging current decreases slowly, and the dynamic room temperature charging acceptance performance of the battery is improved. The formula includes the following ingredients in parts by weight:

[0023]

[0024] The apparent density of the positive lead paste is increased to 4.65±0.05g / cm3. The utilization rate of the positive lead paste is reduced to 46% to 48%, which reduces the vulcanization rate of the positive plate during battery use.

[0025] The dynamic normal temperature charging acceptance method is different from the national standard charging acceptance method. One is charging from 30% SOC to 90% SOC at 25℃, with a constant voltage of 14V and a current limit of 120A. The other is 50% SOC stored at 0℃ for 20h and a charging current value of 10min. Only after the positive electrode increases the apparent density of the lead paste, the use of TBAB will be effective. The lower the voltage platform, the longer the duration of reaching the current limit, and the more electricity can be charged per unit time.

[0026] For the positive plate, the volume of the positive plate will shrink after deep discharge and recharging. The higher the apparent density, the greater the binding force between the active substances and the adhesion to the grid, so the rate of sulfuric acid generation will also decrease, and the battery voltage will increase slowly. Using TBAB can further reduce the rate of sulfuric acid generation (the retention value of SO42- ions increases).

[0027] The negative electrode formula is optimized and designed, and plastic-grade conductive carbon black is added to the formula, which has the characteristics of small particle size, high structure, pure surface, roughness, voids and hollows, and can effectively form a three-dimensional network structure in the insulator, effectively improving the conductivity. Improve the conductivity between active substances and improve the dynamic room temperature charging acceptance performance of the battery. At the same time, high-purity humic acid (Fe content ≤ 300PPM) is used to reduce the water loss rate of sulfuric acid electrolyte. And increase the barium sulfate content to increase the lead sulfate conversion rate on the surface of the negative plate during charging. The formula includes the following ingredients in parts by weight:

[0028]

[0029]

[0030] And increase the apparent density of negative lead paste to 4.50±0.05g / cm 3 . Reduce the utilization rate of negative electrode lead paste, that is, 53%-55%, improve the dynamic room temperature charging acceptance performance, and slow down the capacity decay.

[0031] The main material of the battery tank is PP material, which will age in the later period of use. When the vehicle is parked, it will still output a leakage current of 1A, and the tank body will generate static electricity. The use of plastic-grade conductive carbon black can play a good anti-static role, avoid discharge caused by charge accumulation, and prevent the battery from being greatly reduced in charge state after being static for a long time. Plastic-grade conductive carbon black is a kind of conductive, high structural performance, irregular aggregate, very small size, nanometer level. The battery discharge depth is too deep, and a coarse lead sulfate layer is formed on the surface of the plate. It cannot receive large current in the early stage of charging, and can only receive large current normally after the lead sulfate layer is eliminated. Adding plastic-grade conductive carbon black, because it is nanometer level, can enable the plate to receive large current and improve charging efficiency.

[0032] The active material ratio is optimized and designed, with thick plates and few sheets, the pole group is 15+16-, and the ratio of the total amount of positive active material to the total amount of negative active material is 1.2-1.3, which can alleviate the softening and shedding rate of the positive active material after the battery is deeply discharged for a long time.

[0033]

[0034] Active material refers to the amount of active material attached to the surface of the positive or negative electrode grid after lead paste is prepared according to the positive or negative electrode formula and then coated.

[0035] Raw board type Active substance mass g / tablet Plate thickness mm Number of plates per pole group Positive electrode (current) 125 2.0 16 Negative electrode (current) 100 1.6 17 Positive electrode (the present invention) 150 2.2 15 Negative electrode (the present invention) 110 1.8 16

[0036] The separator type is optimized and designed, using a glass fiber bag separator, which can store the necessary amount of electrolyte in the porous separator between the plates to ensure high conductivity and battery reaction requirements, reduce plate polarization, and improve the continuous discharge capacity under deep discharge environment.

[0037] The electrolyte is optimized and designed by adding benzyl silicone oil, which has high thermal stability and antioxidant properties. It adheres to the surface of the electrolyte to form an insulating layer, reducing the rate of water loss of the electrolyte at high temperature. The addition amount is 0.5%. Adding aluminum acetylacetonate to the electrolyte as a cross-linking agent can slow down the gel stratification problem caused by silica in the electrolyte, improve the uniformity of the upper and lower electrolytes, and enhance the battery's parking condition cycle capacity in the later stage of use. The addition amount is 0.2%. After the first acid addition, charging and formation, without acid collapse, the second acid addition is performed to obtain a finished battery. The mass fractions of each component in the electrolyte during the first acid addition are: dilute sulfuric acid 98.8%, SiO2 0.5%, benzyl silicone oil 0.5%, and aluminum acetylacetonate 0.2%. The density of the electrolyte after the first acid addition is 1.240±0.002g / cm 3 Only dilute sulfuric acid is added for the secondary acid addition. The raw material ratio of dilute sulfuric acid is: 1.84g / ml H2S04 is 1L, H20 is 3.31L, and Na2S04 is 43.77g.

[0038] Silica gels quickly and becomes less stable as the ambient temperature rises. In the early stage of formation, before power is supplied, the gel will block the plate porosity and reduce the plate discharge capacity. Adding aluminum acetylacetonate can increase the thermal stability of silica and reduce the gelation speed.

[0039] The surface treatment material of the battery tank is optimized and designed. A layer of flexible phase change material is attached to the wall of the battery tank. Olefin block copolymer is used as the supporting material and melted and mixed with paraffin. Expanded graphite is selected as a thermal conductivity enhancer to improve the thermal conductivity of the phase change material and enhance the structural stability of the fixed phase change material. In a low temperature environment of -10℃, the thermal insulation capacity of the battery tank can be improved, and the internal temperature can be increased by up to 5.7℃; thereby improving the capacity attenuation in a low temperature environment. In a high temperature environment of 40℃, the high latent heat in the phase change process can be used to temporarily store the internal heat generated, which plays a role in reducing the internal temperature of the battery, and the maximum temperature drop can reach 2.9℃. Thus, the capacity attenuation in a high temperature environment is improved.

[0040] The beneficial effects of the present invention are: a parking air conditioning battery that meets the needs of short-distance driving, with low lead consumption cost, slow capacity decay, and low water loss rate, while focusing on improving the dynamic normal temperature charging acceptance performance (the time required to charge from 30% SOC to 90% SOC) to within 150 minutes. And low SOC cycle performance (30%-40% SOC) to more than 24 units (this number of units corresponds to the vehicle not fully charging the battery for 50 consecutive days). Improve the comfort of end customers, reduce unnecessary quality return losses, and solve industry problems. BRIEF DESCRIPTION OF THE DRAWINGS

[0041] Figure 1 It is a comparison diagram of the terminal voltage of the combination control example and the combination embodiment after 50mA discharge for 24h. DETAILED DESCRIPTION

[0042] The technical solutions in the embodiments of the present invention are described clearly and completely below. The described embodiments are only a part of the embodiments of the present invention, not all of the embodiments. The following description of at least one exemplary embodiment is actually only illustrative and is by no means intended to limit the present invention and its application or use. All other embodiments obtained by ordinary technicians in this field without creative work based on the embodiments of the present invention are within the scope of protection of the present invention.

[0043] The technologies, methods and equipment known to ordinary technicians in the relevant fields may not be discussed in detail, but in appropriate cases, the technologies, methods and equipment should be considered as part of the authorization specification. The present invention mainly studies the design and process implementation of the positive grid, positive electrode formula, negative electrode formula, active material ratio, separator type, electrolyte additives, and battery tank surface treatment materials of the battery. Other processes are not mentioned, which are the same as the existing conventional product implementation methods.

[0044] The present invention provides a parking air-conditioning battery that meets the needs of short-distance driving. A layer of flexible phase change material is attached to the wall of the battery slot, and an olefin block copolymer is used as a supporting material and melted and mixed with paraffin. Expanded graphite is selected as a thermal conductivity enhancer to improve the thermal conductivity of the phase change material while enhancing the structural stability of the fixed phase change material. In a low temperature environment of -10°C, the thermal insulation capacity of the battery slot can be improved, and the internal temperature can be increased by up to 5.7°C; thereby improving the capacity attenuation in a low temperature environment. In a high temperature environment of 40°C, the high latent heat in the phase change process can be used to temporarily store the internal heat generated, which plays a role in reducing the internal temperature of the battery, and the maximum temperature drop can reach 2.9°C. Thereby improving the capacity attenuation in a high temperature environment.

[0045] The present invention discloses a parking air-conditioning battery that meets the needs of short-distance driving, which adopts a thick plate and few-piece design, with a pole group combination of 15+16-, and a positive and negative active material ratio of 1.2-1.3. Alleviate the softening and shedding rate of the positive active material after the battery is deeply discharged for a long time. By using a glass fiber bag separator, a necessary amount of electrolyte can be stored in the porous separator between the pole plates to ensure high conductivity and battery reaction requirements. Reduce the polarization of the pole plates, and at the same time improve the continuous discharge capacity under a deep discharge environment. Adding aluminum acetylacetonate to the electrolyte as a cross-linking agent can slow down the gel stratification problem caused by silicon dioxide in the electrolyte, improve the uniformity of the upper and lower electrolytes, and improve the battery's cycling ability in parking conditions in the later stage of use. The following amounts are all parts by mass unless otherwise specified.

[0046] Comparative Example 1:

[0047] ①Use conventional tank;

[0048] ②Do not use flexible phase change materials to treat the tank surface;

[0049] ③Use conventional Pb-Ca alloy for positive electrode grid;

[0050] ④ The positive electrode uses a conventional deep cycle formula, and the lead paste apparent density is 4.50±0.05g / cm 3 ;

[0051] ⑤ The negative electrode uses a conventional deep cycle formula, and the lead paste apparent density is 4.45±0.05g / cm 3 ;

[0052] ⑥ Cluster combination 16+17-, the ratio of positive and negative active materials is 1.09;

[0053] ⑦Use double-sided PE separator;

[0054] ⑧ Add silicon dioxide to the electrolyte in an amount of 0.5% (mass fraction);

[0055] ⑨The open circuit voltage of the finished battery is 12.85V.

[0056] Comparative Example 2:

[0057] ①Use mesh shell tank;

[0058] ②Do not use flexible phase change materials to treat the tank surface;

[0059] ③Use conventional Pb-Ca alloy for positive electrode grid;

[0060] ④ The positive electrode uses a conventional deep cycle formula, and the lead paste apparent density is 4.50±0.05g / cm 3 ;

[0061] ⑤ The negative electrode uses a conventional deep cycle formula, and the lead paste apparent density is 4.45±0.05g / cm 3 ;

[0062] ⑥ Cluster combination 16+17-, the ratio of positive and negative active materials is 1.09;

[0063] ⑦Use double-sided PE separator;

[0064] ⑧ Add silicon dioxide to the electrolyte in an amount of 0.5% (mass fraction);

[0065] ⑨The open circuit voltage of the finished battery is 12.85V.

[0066] Embodiment 1:

[0067] ①Use conventional tank;

[0068] ②Use flexible phase change material to treat the surface of the tank;

[0069] ③Use conventional Pb-Ca alloy for positive electrode grid;

[0070] ④ The positive electrode uses a conventional deep cycle formula, and the lead paste apparent density is 4.50±0.05g / cm 3 ;

[0071] ⑤ The negative electrode uses a conventional deep cycle formula, and the lead paste apparent density is 4.45±0.05g / cm 3 ;

[0072] ⑥ Cluster combination 16+17-, the ratio of positive and negative active materials is 1.09;

[0073] ⑦Use double-sided PE separator;

[0074] ⑧ Add silicon dioxide to the electrolyte in an amount of 0.5% (mass fraction);

[0075] ⑨The open circuit voltage of the finished battery is 12.85V.

[0076] Improvement effect comparison:

[0077] The same model and batch of batteries were tested for capacity cycle testing, and the results are as follows:

[0078]

[0079] It can be seen from the test capacity data in the above table that by adopting the optimized design of the battery slot surface treatment material of the present invention, the three-time capacity attenuation is reduced by 5% in a low temperature environment of -10°C, and the three-time capacity attenuation is reduced by 4% in a high temperature environment of 40°C, which has a certain improvement on the battery capacity attenuation.

[0080] The present invention discloses a parking air conditioning battery that meets the needs of short-distance driving. The new Mg-Zn-Al alloy is used. The Ca content of the grid alloy is appropriately increased, and an intermediate phase with a very high melting point is formed in the matrix. These phases are not easy to decompose at high temperatures, and can effectively prevent the movement of grain boundaries, so that the high-temperature mechanical properties of the alloy, especially the creep resistance, are significantly improved. At the same time, the Ag content is appropriately increased, which can effectively reduce the water loss rate of the electrolyte. Adding phenylmethyl silicone oil to the electrolyte has high thermal stability and oxidation resistance, adheres to the surface of the electrolyte to form an insulating layer, and reduces the water loss rate of the electrolyte at high temperatures.

[0081] Comparative Example 3:

[0082] ①Use flexible phase change material to treat the surface of the tank;

[0083] ②Use conventional Pb-Ca alloy for positive electrode grid;

[0084] ③ The positive electrode uses a conventional deep cycle formula, and the lead paste apparent density is 4.50±0.05g / cm 3 ;

[0085] ④ The negative electrode uses a conventional deep cycle formula, and the lead paste apparent density is 4.45±0.05g / cm 3 ;

[0086] ⑤ Cluster combination 16+17-, the ratio of positive and negative active materials is 1.09;

[0087] ⑥Use double-sided PE separator;

[0088] ⑦ Add silicon dioxide to the electrolyte in an amount of 0.5% (mass fraction);

[0089] ⑧The open circuit voltage of the finished battery is 12.85V.

[0090] Comparative Example 4:

[0091] ①Use flexible phase change material to treat the surface of the tank;

[0092] ② Use positive grid alloy to optimize design;

[0093] ③ The positive electrode uses a conventional deep cycle formula, and the lead paste apparent density is 4.50±0.05g / cm 3 ;

[0094] ④ The negative electrode uses a conventional deep cycle formula, and the lead paste apparent density is 4.45±0.05g / cm 3 ;

[0095] ⑤ Cluster combination 16+17-, the ratio of positive and negative active materials is 1.09;

[0096] ⑥Use double-sided PE separator;

[0097] ⑦ Add silicon dioxide to the electrolyte in an amount of 0.5% (mass fraction);

[0098] ⑧The open circuit voltage of the finished battery is 12.80V.

[0099] Embodiment 2:

[0100] ①Use flexible phase change material to treat the surface of the tank;

[0101] ② Use positive grid alloy to optimize design;

[0102] ③ The positive electrode uses a conventional deep cycle formula, and the lead paste apparent density is 4.50±0.05g / cm 3 ;

[0103] ④ The negative electrode uses a conventional deep cycle formula, and the lead paste apparent density is 4.45±0.05g / cm 3 ;

[0104] ⑤ Cluster combination 16+17-, the ratio of positive and negative active materials is 1.09;

[0105] ⑥Use double-sided PE separator;

[0106] ⑦ Add silicon dioxide to the electrolyte in an amount of 0.5% (mass fraction);

[0107] ⑧ Add phenylmethyl silicone oil to the electrolyte in an amount of 0.5% (mass fraction);

[0108] ⑨The open circuit voltage of the finished battery is 12.80V.

[0109] Improvement effect comparison:

[0110] The same model and batch of batteries were tested for water loss and SAE J2801 life test. The results are as follows:

[0111]

[0112] It can be seen from the test data in the above table that by adopting the optimized design of the positive grid alloy of the battery of the present invention and adding benzyl silicone oil to the electrolyte, the water loss of the public is reduced by 2.72g / Ah, and the SAE J2801 life is increased by 3 units. There is a significant improvement in water loss, positive grid growth and corrosion at high temperature.

[0113] Comparative Example 5:

[0114] ①Use flexible phase change material to treat the surface of the tank;

[0115] ② Use positive grid alloy to optimize design;

[0116] ③ The positive electrode uses a conventional deep cycle formula, and the lead paste apparent density is 4.50±0.05g / cm 3 ;

[0117] ④ The negative electrode uses a conventional deep cycle formula, and the lead paste apparent density is 4.45±0.05g / cm 3 ;

[0118] ⑤ Cluster combination 16+17-, the ratio of positive and negative active materials is 1.09;

[0119] ⑥Use double-sided PE separator;

[0120] ⑦ Add silicon dioxide to the electrolyte in an amount of 0.5% (mass fraction);

[0121] ⑧ Add phenylmethyl silicone oil to the electrolyte in an amount of 0.5% (mass fraction);

[0122] ⑨The open circuit voltage of the finished battery is 12.80V.

[0123] Comparative Example 6:

[0124] ①Use flexible phase change material to treat the surface of the tank;

[0125] ② Use positive grid alloy to optimize design;

[0126] ③ The positive electrode uses a conventional deep cycle formula, and the lead paste apparent density is 4.50±0.05g / cm 3 ;

[0127] ④ The negative electrode uses a conventional deep cycle formula, and the lead paste apparent density is 4.45±0.05g / cm 3 ;

[0128] ⑤ The cluster is matched with 15+16-, and the ratio of positive and negative active materials is 1.2;

[0129] ⑥Use fiberglass bag partitions;

[0130] ⑦ Add silicon dioxide to the electrolyte in an amount of 0.5% (mass fraction);

[0131] ⑧ Add phenylmethyl silicone oil to the electrolyte in an amount of 0.5% (mass fraction);

[0132] ⑨The open circuit voltage of the finished battery is 12.80V.

[0133] Embodiment 3:

[0134] ①Use flexible phase change material to treat the surface of the tank;

[0135] ② Use positive grid alloy to optimize design;

[0136] ③ The positive electrode uses a conventional deep cycle formula, and the lead paste apparent density is 4.50±0.05g / cm3;

[0137] ④ The negative electrode uses a conventional deep cycle formula, and the lead paste apparent density is 4.45±0.05g / cm3;

[0138] ⑤ The cluster is matched with 15+16-, and the ratio of positive and negative active materials is 1.2;

[0139] ⑥Use fiberglass bag partitions;

[0140] ⑦ Add silicon dioxide to the electrolyte in an amount of 0.5% (mass fraction);

[0141] ⑧ Add phenylmethyl silicone oil to the electrolyte in an amount of 0.5% (mass fraction);

[0142] ⑨ Add aluminum acetylacetonate to the electrolyte in an amount of 0.2% (mass fraction);

[0143] ⑩The open circuit voltage of the finished battery is 12.80V.

[0144] Improvement effect comparison:

[0145] The same model and batch of batteries were tested for national standard cycle endurance II and parking condition performance tests. The results are as follows:

[0146] Implementation Comparative Example 5 Comparative Example 6 Example 3 National standard cycle durability II unit Unit 5 Unit 8 Unit 10 Parking mode times 150 times 170 times 200 times

[0147] It can be seen from the test data in the above table that the optimized design of the ratio of active materials in the battery, the optimized design of the separator type and the addition of aluminum acetylacetonate in the electrolyte of the present invention can improve the national standard cycle durability II by 5 units and the parking condition by 50 times, thereby improving the continuous discharge capacity under deep discharge environment.

[0148] The present invention provides a parking air conditioning battery that meets the needs of short-distance driving. Tetrabutylammonium bromide (TBAB) powder organic salt and a phase transfer catalyst are added to the positive electrode lead paste formula, which can transfer the reactant of the aqueous phase (or organic phase) to the organic phase (or aqueous phase). The retention value of the anion is increased, and the separation degree of the anion and the coexisting ion is also increased. In addition, the voltage platform during battery charging is reduced, the charging current decreases slowly, and the dynamic room temperature charging acceptance performance of the battery is improved.

[0149] Adding plastic-grade conductive carbon black to the negative lead paste formula has the characteristics of small particle size, high structure, pure surface, roughness, voids and hollows, which can effectively form a three-dimensional network structure in the insulator, effectively improve the conductivity, improve the conductivity between active substances, and improve the dynamic room temperature charging acceptance performance of the battery.

[0150] Comparative Example 7:

[0151] ①Use flexible phase change material to treat the surface of the tank;

[0152] ② Use positive grid alloy to optimize design;

[0153] ③ The positive electrode uses a conventional deep cycle formula, and the lead paste apparent density is 4.50±0.05g / cm3;

[0154] ④ The negative electrode uses a conventional deep cycle formula, and the lead paste apparent density is 4.45±0.05g / cm3;

[0155] ⑤ The cluster is matched with 15+16-, and the ratio of positive and negative active materials is 1.2;

[0156] ⑥Use fiberglass bag partitions;

[0157] ⑦ Add silicon dioxide to the electrolyte at a rate of 0.5%;

[0158] ⑧ Add phenylmethyl silicone oil to the electrolyte in an amount of 0.5%;

[0159] ⑨ Add aluminum acetylacetonate to the electrolyte in an amount of 0.2%;

[0160] ⑩The open circuit voltage of the finished battery is 12.80V.

[0161] Comparative Example 8:

[0162] ①Use flexible phase change material to treat the surface of the tank;

[0163] ② Use positive grid alloy to optimize design;

[0164] ③Use the positive electrode formula to study and optimize the design, the lead paste apparent density is 4.65±0.05g / cm3;

[0165] ④ The negative electrode uses a conventional deep cycle formula, and the lead paste apparent density is 4.45±0.05g / cm3;

[0166] ⑤ The cluster is matched with 15+16-, and the ratio of positive and negative active materials is 1.2;

[0167] ⑥Use fiberglass bag partitions;

[0168] ⑦ Add silicon dioxide to the electrolyte in an amount of 0.5% (mass fraction);

[0169] ⑧ Add phenylmethyl silicone oil to the electrolyte in an amount of 0.5% (mass fraction);

[0170] ⑨ Add aluminum acetylacetonate to the electrolyte in an amount of 0.2% (mass fraction);

[0171] ⑩The open circuit voltage of the finished battery is 12.80V.

[0172] Embodiment 4:

[0173] ①Use flexible phase change material to treat the surface of the tank;

[0174] ② Use positive grid alloy to optimize design;

[0175] ③Use the positive electrode formula to study and optimize the design, the lead paste apparent density is 4.65±0.05g / cm3;

[0176] ④ Use the negative electrode formula to study and optimize the design, the lead paste apparent density is 4.50±0.05g / cm3;

[0177] ⑤ The cluster is matched with 15+16-, and the ratio of positive and negative active materials is 1.2;

[0178] ⑥Use fiberglass bag partitions;

[0179] ⑦ Add silicon dioxide to the electrolyte in an amount of 0.5% (mass fraction);

[0180] ⑧ Add phenylmethyl silicone oil to the electrolyte in an amount of 0.5% (mass fraction);

[0181] ⑨ Add aluminum acetylacetonate to the electrolyte in an amount of 0.2% (mass fraction);

[0182] ⑩The open circuit voltage of the finished battery is 12.80V.

[0183] Improvement effect comparison:

[0184] Test the batteries of the same model and batch to conduct dynamic room temperature charging acceptance performance test. The test method is as follows:

[0185] ① Within 1 to 5 hours after the battery is fully charged (at 25℃±1℃, charge with 2In(A) current until the average voltage of the single battery reaches 2.4V, and then continue charging for 5 hours), and keep it at 25℃±2℃ ambient temperature, discharge 70% of the actual capacity (maximum actual capacity) with Io(A) current.

[0186] ②After discharge, fix the battery on the swing machine with a vibration test fixing pressure rod, set the parameters to swing 30 times per minute, and the swing angle is 15°. Charge to 60% of the actual maximum capacity with a constant voltage of 14V and a current limit of 120A, and record the charging time.

[0187] The test results are as follows:

[0188]

[0189] It can be seen from the test data in the above table that the positive electrode formula research and optimization design and the negative electrode formula research and optimization design of the battery of the present invention are adopted. The dynamic normal temperature charging acceptance time is shortened by 85 minutes. The dynamic normal temperature charging acceptance performance of the lead-acid flooded parking air conditioning battery is greatly improved.

[0190] Combination comparison ratio:

[0191] ①Use conventional tank;

[0192] ②Do not use flexible phase change materials to treat the tank surface;

[0193] ③Use conventional Pb-Ca alloy for positive electrode grid;

[0194] ④ The positive electrode uses a conventional deep cycle formula, and the lead paste apparent density is 4.50±0.05g / cm 3 ;

[0195] ⑤ The negative electrode uses a conventional deep cycle formula, and the lead paste apparent density is 4.45±0.05g / cm 3 ;

[0196] ⑥ Cluster combination 16+17-, the ratio of positive and negative active materials is 1.09;

[0197] ⑦Use double-sided PE separator;

[0198] ⑧ The amount of silicon dioxide added to the electrolyte is 0.5% (mass fraction);

[0199] ⑨The open circuit voltage of the finished battery is 12.80V.

[0200] Electrolyte formula in the combined comparative example:

[0201] Raw material ratio for preparing dilute sulfuric acid:

[0202] Density of dilute sulfuric acid (g / ml 25℃) <![CDATA[1.84g / ml H2S04(L)]]> <![CDATA[H20(L)]]> <![CDATA[Na2S04(g)]]> 1.240±0.002 1 3.31 43.77

[0203] Dilute sulfuric acid (%) <![CDATA[SiO2(%)]]> <![CDATA[Electrolyte density (g / cm 3 )]]> 99.5 0.5 1.240±0.002

[0204] Combination embodiment:

[0205] ①Use flexible phase change material to treat the surface of the tank;

[0206] ② Use positive grid alloy to optimize design;

[0207] ③Use the positive electrode formula to optimize the design, the lead paste density is 4.65±0.05g / cm 3 ;

[0208] ④ Use the negative electrode formula to study and optimize the design, the lead paste density is 4.50±0.05g / cm 3 ;

[0209] ⑤ The cluster is matched with 15+16-, and the ratio of positive and negative active materials is 1.2;

[0210] ⑥Use fiberglass bag partitions;

[0211] ⑦ Add silicon dioxide to the electrolyte in an amount of 0.5% (mass fraction);

[0212] ⑧ Add phenylmethyl silicone oil to the electrolyte in an amount of 0.5% (mass fraction);

[0213] ⑨ Aluminum acetylacetonate was added to the electrolyte in an amount of 0.2% (mass fraction).

[0214] ⑩The open circuit voltage of the finished battery is 12.80V.

[0215] Optimize electrolyte formulation:

[0216] Density of dilute sulfuric acid (g / ml 25℃) <![CDATA[1.84g / ml H2S04(L)]]> <![CDATA[H20(L)]]> <![CDATA[Na2S04(g)]]> 1.240±0.002 1 3.31 43.77

[0217] Dilute sulfuric acid (%) <![CDATA[SiO2(%)]]> Benzyl silicone oil (%) Aluminum acetylacetonate (%) <![CDATA[Electrolyte density (g / cm 3 )]]> 98.8 0.5 0.5 0.2 1.240±0.002

[0218] Effect comparison:

[0219] Test the batteries of the same model and batch for 30% to 40% low SOC cycle performance test. The test method is as follows:

[0220] ① Pretreatment: discharge with I20 for 12 hours and let stand for 16 hours;

[0221] ②Step 1: Discharge with I20 for 2 hours, and immediately discharge at 330A (range limit of detection center circuit) at room temperature for 10S;

[0222] ③Step 2: 50mA discharge for 24h;

[0223] ④Step 3: Constant voltage 14.2V (current limit 100A), charge to 10% of actual capacity.

[0224] ⑤Step 4: 50mA discharge for 24h;

[0225] ⑥Step 5: Repeat steps 1 to 4, and shut down the machine when the discharge voltage in step 2 is lower than 10V.

[0226] Before testing the battery, it must be fully charged according to national standards, and the life test temperature is 25°C.

[0227] The test results are as follows:

[0228]

[0229] It can be seen from the test data in the above table that by adopting the battery combination scheme of the present invention, the 20hr capacity attenuation, Volkswagen water loss, J2801 life, national standard cycle endurance II, parking condition, dynamic room temperature charging acceptance and low SOC cycle test are all improved to a certain extent.

[0230] The above is a detailed introduction to a parking air conditioning battery that meets the needs of short-distance driving provided by an embodiment of the present invention. Specific examples are used in this article to illustrate the principles and implementation methods of the present invention. The description of the above embodiments is only used to help understand the method of the present invention and its core idea; at the same time, for general technical personnel in this field, according to the idea of ​​the present invention, there will be changes in the specific implementation method and application scope. In summary, the content of this specification should not be understood as a limitation on the present invention.

Claims

1. A flooded parking air conditioning battery that meets the needs of short-distance driving, characterized in that: It includes a battery tank, a positive electrode, a negative electrode, a separator, and an electrolyte; the positive electrode grid alloy of the positive electrode uses a Mg-Zn-Al alloy, and the mass percentages of the various components of the alloy are as follows: The positive electrode lead paste formula includes the following components in parts by weight: Increase the apparent density of positive lead paste to 4.65±0.05g / cm 3 , reduce the utilization rate of positive lead paste to 46% to 48%; The negative electrode formulation includes the following components in parts by weight: Increase the apparent density of negative lead paste to 4.50±0.05g / cm 3 , reduce the utilization rate of negative electrode lead paste to 53% to 55%; The ratio of the total amount of positive electrode active material to the total amount of negative electrode active material in the pole group is 1.2-1.3; The mass fractions of the components in the electrolyte are: 98.8% of dilute sulfuric acid, 0.5% of SiO2, 0.5% of benzyl silicone oil, and 0.2% of aluminum acetylacetonate.

2. The flooded parking air conditioning battery that meets the short-distance driving requirements according to claim 1 is characterized in that: The separators are glass fiber bag separators.

3. The flooded parking air conditioning battery that meets the short-distance driving requirements according to claim 1, characterized in that: A layer of flexible phase change material is attached to the wall of the battery container, with olefin block copolymer as the supporting material, melted and mixed with paraffin, and expanded graphite is used as the thermal conductivity enhancer.

4. The flooded parking air conditioning battery that meets the short-distance driving requirements according to claim 1, characterized in that: The pole group is composed of 15 positive plates and 16 negative plates. The active substance mass of each positive plate is 150g, and the thickness of the positive plate is 2.2mm. The active substance mass of each negative plate is 110g, and the thickness of the negative plate is 1.8mm.

5. The flooded parking air conditioning battery that meets the short-distance driving requirements according to claim 1, characterized in that: The raw material ratio of the dilute sulfuric acid is: 1.84g / ml H2S04 is 1L, H20 is 3.31L, and Na2S04 is 43.77g.

6. The flooded parking air conditioning battery that meets the short-distance driving requirements according to claim 1, characterized in that: The density of the electrolyte after acid addition is 1.240±0.002g / cm 3 .